A COMPARATIVE STUDY OF THE IMPACT OF SHRIMADBHAGVATGITA PHILOSOPHY ON SPIRITUAL INTELLIGENCE AND PERSONAL VALUES ​​OF STUDENTS - Sharma, Geetika; Sharaf, Sangeeta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Srimad Bhagavad Gita is such a unique text of Indian philosophy, which not only defines religiosity, but also deeply affects the practical and spiritual aspects of life. The objective of this research is to do a comparative study of the impact of the philosophy of Srimad Bhagavad Gita on the spiritual intelligence and personal values ​​of students. Two groups were selected under the study. The first group was involved in the regular study of the Gita and the second group followed only the general curriculum. After this, a comparative analysis of the moral and spiritual development of both the groups was done. The study found that the students who read the Gita developed more qualities like self-awareness, empathy, and morality. These students also showed significant improvement in stress management, decision-making ability, and positive attitude towards life. In contrast, this improvement was found to be relatively less in the students who did not study the Gita. This research proves that the study of Srimad Bhagavad Gita not only provides spiritual perspective to the students, but also strengthens their personal and social values.